Block Shear Tests in High-Strength Steel Angles - Gross, Jeremy M.; Orbison, James G.; Ziemian, Ronald D. (Engineering Journal, 1995)
Full-scale tests of A588 Grade 50 single-angle tension members, with bolted connections designed to fail in block shear, were conducted. Maximum loads were compared with those predicted by the current American Institute of Steel Construction (AISC) Load and Resistance Factor Design (LRFD) and Allowable Stress Design (ASD) Specifications. It was found that both methods were very accurate in predicting the experimental load capacities. However, the procedure provided in the first edition of the LRFD Specification is shown to consistently, and in some cases significantly, overestimate the nominal failure loads. That procedure is adequate, however, when the resistance factor is applied and design resistance is compared.